2019
DOI: 10.1503/cmaj.181238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiovascular and cerebrovascular health events on work and earnings: a population-based retrospective cohort study

Abstract: S erious acute health events can be life-altering, because survivors can experience lasting reductions in functional status and quality of life. The ability to work and earn income-labour market outcomes-are important patientcentred outcomes 1 for individuals of working age, influencing economic well-being, sense of self and quality of life. 2,3 Health events may start a cascade where new disability causes earnings losses, which contribute to cost-related nonadherence to medication, 4 which contributes to wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Previous studies have shown that many stroke survivors experience long-lasting reductions in their ability to work and earn income (11,29,30). One of the most consistent predictors of stroke survivors return to work is stroke severity (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that many stroke survivors experience long-lasting reductions in their ability to work and earn income (11,29,30). One of the most consistent predictors of stroke survivors return to work is stroke severity (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…During the recent decades there has been a signi cant increase in the incidence of stroke survivors in working ages (10). Many working-age stroke survivors perceive a reduction in their ability to work after the stroke onset (11). Economic theory suggests that couples often share their resources and make joint decisions about their work (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many stroke survivors experience long-lasting reductions in their ability to work and earn income [12,30,31]. One of the most consistent predictors of stroke survivors return to work is stroke severity [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…During the recent decades there has been a significant increase in the incidence of stroke survivors in working ages [11]. Many working-age stroke survivors perceive a reduction in their ability to work after the stroke onset [12]. Economic theory suggests that couples often share their resources and make joint decisions about their work [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…During the recent decades there has been a signi cant increase in the incidence of stroke survivors in working ages (11). Many working-age stroke survivors perceive a reduction in their ability to work after the stroke onset (12). Economic theory suggests that couples often share their resources and make joint decisions about their work (13,14).…”
Section: Introductionmentioning
confidence: 99%